Language teachers’ identity development post COVID-19: a transformative learning perspective - Alosaimi, Muna (Frontiers in Education, 2023)
The COVID-19 pandemic has significantly disrupted the educational sector, leading to profound changes in teachers’ roles and identities. While these disruptions have been challenging, they also offer a unique opportunity for teachers to redefine and evolve their traditional roles and practices. This study, grounded in the poststructuralist perspective of teacher identity, investigates the impact of COVID-19 on the professional identities of seven EFL teachers at a Saudi university post-school reopening. Mezirow’s Transformative Learning framework was utilized to trace the transformations of teachers’ identities, with the pandemic serving as the catalyst for reflection and change. Teachers’ experiences were captured using narrative inquiry and Life Story Interviews, and analyzed via reflexive thematic analysis with an emphasis on professional agency as a conceptual lens. The analysis revealed three key dynamics that characterized the transformation in professional identity during these times: delegitimization, reconstruction, and empowerment. These insights contribute to the teacher education literature by offering a nuanced understanding of identity transformation and by proposing strategies to support teacher identity development in challenging contexts.